2019
DOI: 10.1002/humu.23746
|View full text |Cite
|
Sign up to set email alerts
|

Proposition of adjustments to the ACMG‐AMP framework for the interpretation of MEN1 missense variants

Abstract: In 2015, the ACMG‐AMP guidelines provided a general procedure for the objective and reproducible classification of genomic variants. While the benefits of this framework are of major importance, its adaptation for locus‐specific use is needed. Multiple Endocrine Neoplasia type 1 (MEN1) occurs due to inactivating mutations in the tumour suppressor gene MEN1, including 20% of missense variants. The classification of these variants may be extremely challenging. Here, we compared the interpretation of the 122 MEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The standards and guidelines published by the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) describe a framework for the classification of sequence variants (19). Adjustments to this framework for the interpretation of MEN1 missense variants has been proposed (20). However both agree that variants of uncertain significance should not be used to guide the clinical management of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The standards and guidelines published by the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) describe a framework for the classification of sequence variants (19). Adjustments to this framework for the interpretation of MEN1 missense variants has been proposed (20). However both agree that variants of uncertain significance should not be used to guide the clinical management of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the majority of Molecular Genetic Laboratories adopt the American College of Medical Genetics and Genomics (ACMG) guidelines to assess variant pathogenicity . These guidelines are intended for the evaluation of penetrant monogenic disorders with well‐established disease‐gene associations and employ a multitiered approach, which considers a number of variant‐ and gene‐specific factors (Table ) . The individual pieces of evidence are then considered in combination, and using predetermined criteria, enable the classification of variant into one of five groups: “benign,” “likely benign,” “uncertain significance,” “likely pathogenic” or “pathogenic” (although these categories are based on estimated probabilities and are not absolute) .…”
Section: Germline Genetic Testing – Selecting the Optimal Testmentioning
confidence: 99%
“… A recent study has proposed locus‐specific adjustments to the ACMG‐AMP guidelines for missense variants in the MEN1 gene which place additional weight on patient phenotype and family history (Romanet et al, Hum Mut 2019) …”
Section: Germline Genetic Testing – Selecting the Optimal Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight sarcomeric genes collectively provide firm molecular diagnoses for ~27% of HCM patients, with a further ~13% of patients carrying VUS in the same genes. It has been suggested that disease and genespecific approaches are needed to improve interpretation [16] and guidelines have been produced for specific genes and/or disease areas [17][18][19][20][21]. Missense variant clustering is a gene-specific metric that falls under the ACMG evidence category PM1('mutational hotspot').…”
Section: Introductionmentioning
confidence: 99%